1987
DOI: 10.5014/ajot.41.8.495
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy in Mental Health: Crisis or Opportunity?

Abstract: For at least a decade, concern has been expressed about the status of occupational therapy in mental health. Increases in the number of new jobs and clinicians have not kept pace with growth in other practice areas. Although growing criticism of the practice of deinstitutionalization and an increased focus on cost-effectiveness have recently become major public policy trends in mental health practice, the psychological and nursing professions have responded creatively in order to expand their influence and pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…(Meeson, 1998 a, b) From the literature it appeared that occupational therapists concentrated on four clinical areas dementia; work rehabilitation; community mental health and forensic psychiatry. (Craik, 1998) There has been concern in the USA about the position of occupational therapy in mental health, with declining numbers of therapists noted (Bonder, 1987, Kleinman 1992, Paul, 1996. In 1986, Barris and Kielhofner surveyed educators who suggested the major problems in mental health were deficiencies in role definition, unifying theory and research validating the profession.…”
Section: Introductionmentioning
confidence: 99%
“…(Meeson, 1998 a, b) From the literature it appeared that occupational therapists concentrated on four clinical areas dementia; work rehabilitation; community mental health and forensic psychiatry. (Craik, 1998) There has been concern in the USA about the position of occupational therapy in mental health, with declining numbers of therapists noted (Bonder, 1987, Kleinman 1992, Paul, 1996. In 1986, Barris and Kielhofner surveyed educators who suggested the major problems in mental health were deficiencies in role definition, unifying theory and research validating the profession.…”
Section: Introductionmentioning
confidence: 99%
“…For at least the last two decades, leaders in the profession have voiced concern regarding the decline in mental health occupational therapy practitioners (Bonder, 1987;Paul, 1996).…”
Section: The Value Of a Mental Health Fieldwork Experiencementioning
confidence: 99%
“…Researchers have attempted to identify factors that have contributed to the decline and have offered recommendations to enrich the psychosocial fieldwork experience, initiate student exposure to mental health occupational therapy practice, and increase the numbers of students participating in mental health fieldwork placements (Atwater & Davis, 1990;Barris & Keilhofner, 1986;Bonder, 1987;Dallis & Starnes, 2004;Ebb & Haimann, 1990;Kautzmann, 1995;Price, 1993). Steele-Smith and Armstrong (2001) suggested that mental health practitioners set up structured fieldwork education programs that emphasize self-directed learning with peers and opportunities for students to lead therapeutic patient groups.…”
Section: The Value Of a Mental Health Fieldwork Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…There are very few published stud ies in which professionals have been surveyed regarding the transition from institutional care to community treatment. The articles published have mainly focused on changed professional roles (Aiken, 1987;Bonder, 1987).…”
Section: Introductionmentioning
confidence: 99%